Biosynthesis of phyto-functionalized silver nanoparticles using olive fruit extract and evaluation of their antibacterial and antioxidant properties - Ullah, Sami; Khalid, Rimsha; Rehman, Muhammad F.; Irfan, Muhammad I.; Abbas, Azhar; Alhoshani, Ali; Anwar, Farooq; Amin, Hatem M. A. (Frontiers in Chemistry, 2023)
The green synthesis of nanomaterials is of utmost interest as it offers an eco-friendly approach over chemical synthetic routes. However, the reported biosynthesis methods are often time-consuming and require heating or mechanical stirring. The current study reports a facile one-pot biosynthesis of silver nanoparticles (AgNPs) mediated by olive fruit extract (OFE) and sunlight irradiation of only 20 s. OFE acts as both a reducing and a capping agent for the formation of OFE-capped AgNPs (AgNPs@OFE). The as-synthesized NPs were systematically characterized by UV-vis spectrometry, Fourier transform infrared (FTIR) spectroscopy, scanning electrochemical microscopy with energy-dispersive X-ray (SEM-EDX), X-ray diffraction (XRD), dynamic light scattering (DLS), and cyclic voltammetry. SEM images confirmed the successful formation of monodispersed spherical AgNPs@OFE of approximately 77 nm. FTIR spectroscopy suggested the involvement of functional groups of phytochemicals from the OFE in the capping and reduction of Ag+ to Ag. The particles revealed excellent colloidal stability as evidenced from the high zeta potential (ZP) value (−40 mV). Interestingly, using the disk diffusion method, AgNPs@OFE revealed higher inhibition efficiency against Gram-negative bacteria (Escherichia coli, Klebsiella oxytoca, and extensively drug-resistant (XDR) Salmonella typhi) than Gram-positive bacteria (Staphylococcus aureus), with Escherichia coli showing the highest inhibition zone of 27 mm. In addition, AgNPs@OFE exhibited maximum potent antioxidant scavenging potential against H2O2, followed by DPPH, O2−, and OH− free radicals. Overall, OFE can be considered an effective source for the sustainable production of stable AgNPs with potential antioxidant and antibacterial activities for biomedical applications.